Photochemical reflectance index and leaf photosynthetic radiation-use-efficiency assessment in Mediterranean trees - Penuelas, J; Llusia, J; Piñol, J; Filella, I (International Journal of Remote Sensing, 1997)
Abstract This Letter presents new data validating the use of the photochemical reflectance index PRI (R570-R531)/(R570 + R531) to assess photosynthetic- radiation-use-efficiency under mild water stress. Gas exchange, fluorescence and the PRI of leaves from the Mediterranean trees Quercus ilex and Phillyrea latifolia growing in the field were followed from spring to summer 1996 in central Catalonia (NE Spain). The same variables were measured in seedlings of these two species and Pistacia lentiscus submitted to progressive drying after witholding irrigation. Except for severely drought damaged plants, significant relations of the reflectance index PRI with fluorescence yield of the photosystem II (Delta F/F' m), non photochemical fluorescence quenching ( qN ) and photosynthetic radiation use efficiency (PRUE) were found, thus indicating a functional relation among these parameters. A simple portable radiometer measuring ground level reflectance at narrow bands centred at 531 and 570nm could instantaneously calculate the PRI index and give the PRUE estimation.
doi: 10.1080/014311697217387
Keywords: Fluorescence (voyant); Gas exchange; photochemical reflectance index PRI; photosynthetic radiation use efficiency